Management Problems in Socio-Economic Systems: Theory, Methodology, Practice - Litvinov A. N., Smirnova I. L., Baranova N. A., Iovleva O. O., Mishulina O. V., Malanina A. A., Mfliarenko O. I., Panina G. V., Gorelova N. S., Lilimberg S. I., Kulakova S. V., Borovkova V. A., Borovkova V. A., Kul'chikova Z. T. (Management Problems in Socio-Economic Systems: Theory, Methodology, Practice, 2019)
today transit to «green» and «digital» economy, to sustainable social-economic development is complex theoretical and practical problem. It is demand to research and develop approaches to structure-technological transformation and modernization of economy and society, mechanisms and instruments of safety transit to the new model of economy. In the research the authors made own interpretation of «digitalization economy», «ecologization economy», indicates factors of digitalization influence on ecologization of economy, present own classification of transit to «green» economy instruments in the digitalization context and the model for integrated assessment of the sustainable environmental-economic development, included the digital competence index.
Keywords: факторы; цифровизация; устойчивое развитие; sustainable development; factors; digitalization; влияние; экологизация; инструменты цифровой трансформации; индекс цифровой грамотности; ecologization; influence; digital transformation instruments; digital competence index